Lymphoma risks in patients with rheumatoid arthritis treated with biological drugs—a Swedish cohort study of risks by time, drug and lymphoma subtype. (18th August 2020) - Hellgren, Karin; Di Giuseppe, Daniela; Smedby, Karin E; Sundström, Christer; Askling, Johan; Baecklund, Eva; ,
Abstract: Objectives: To estimate the association between biological DMARDs (bDMARDs; overall and by drug) as used in RA and the risk of malignant lymphomas including subtypes. Methods: By linking nationwide Swedish registers we identified cohorts of patients with RA initiating treatment with a bDMARD ( n  = 16 392), bDMARD-naïve ( n  = 55 253), an age- and sex-matched general population comparator cohort ( n  = 229 047), and all incident lymphomas 2001–16. We used Cox regression to calculate hazard ratios (HRs) of lymphoma taking calendar period and other factors into account. Results: There were 82 lymphomas among the bDMARD-treated patients with RA, crude incidence rate 76/100 000 person-years, and 310 lymphomas among the bDMARD-naïve patients with RA, crude incidence rate 90/100 000 person-years. This resulted in an adjusted HR (aHR) associated with bDMARD treatment ( vs not) of 1.08 (95% CI: 0.83, 1.41). The corresponding aHR for bDMARD-treated and bDMARD-naïve vs the general population was 1.65 (95% CI: 1.31, 2.08) and 1.56 (95% CI: 1.37, 1.78) respectively. Restricting follow-up period to after 2006, the aHR of lymphoma for patients with RA starting a first bDMARD vs bDMARD-naïve was 0.69 (95% CI: 0.47, 1.00), and for bDMARD treated vs patients with RA switching from one conventional synthetic DMARDs to another, aHR was 0.46 (95% CI: 0.28, 0.73). There were no signals of different risks with any particular TNF inhibitor (TNFi) agent. We found no different lymphoma subtype pattern following bDMARD therapy. Conclusion: Treatment with bDMARDs, including both TNFi and non-TNFi bDMARDs, does not further increase the lymphoma risk in RA; instead, bDMARD treatment may actually reduce the excess lymphoma risk in RA.